EFEKTIVITAS PELAYANAN PROGRAM PENYAKIT KRONIS DALAM MENGONTROL TEKANAN DARAH PADA PESERTA PROLANIS YANG MENGALAMI HIPERTENSI - Trismadani Erlina Putri; Muhammad Syamsu Hidayat; Tri Ani Marwati (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Hypertension is one of the causes of the highest morbidity and mortality rates in Indonesia. So that the needs of people who suffer from hypertension for health services are increasing. Prolanis is controlling the health condition of the hypertension sufferer program under the auspices of BPJS. The purpose of this study is to analyze the effectiveness of Prolanis in controlling blood pressure in prolanis participants. The method used in this article is a systematic literature review. The literature review searches using Google Scholar, Pubmed, and Researchgate databases in the 2017-2022 range with the search keywords are “Tekanan Darah” AND “Program Penanggulangan Penyakit Kronis” OR “Prolanis” AND “Hipertensi”, “Blood Pressure” AND “Chronic Disease Management Programs” OR “Prolanis” AND “Hypertension” found 8 articles met the selection criteria based. The results of the study of 8 articles showed that Prolanis activities could effectively control the blood pressure of Prolanis participants if they were carried out actively and routinely. The implementation of Prolanis activities, namely, medical consultations, group education and club activities, SMS gateway reminders, and recommended home visits can be carried out in all Prolanis first health care facilities in Indonesia in preventing and controlling blood pressure of people with hypertension.